1986
DOI: 10.1063/1.97287
|View full text |Cite
|
Sign up to set email alerts
|

Focused ion beam induced deposition of gold

Abstract: A finely focused ion beam is scanned over a surface on which a local gas ambient of dimethyl gold hexafluoro acetylacetonate is created by a directed miniature nozzle. The incident ions induce the selective deposition of gold along the path traced by the beam. The 15-keV Ga+ ion beam current is 100 pA and the beam diameter is 0.5 μm. Gold lines of 0.5 μm width and Gaussian profile are written. The film growth rate corresponds to five atoms deposited per incident ion. The focused ion beam deposited films contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(39 citation statements)
references
References 10 publications
1
38
0
Order By: Relevance
“…Charged particle beam-induced deposition (Matsui et al 2000, Shedd et al 1986) is widely used, for example in focused ion-beam (FIB) technology for the formation of metal layers and for the repair of semiconductor circuits. To achieve spatial resolutions better than 100 nm, electron beam-induced deposition (EBID) and etching (EBIE) have been recently explored as a technique for fabrication or repair.…”
Section: Introductionmentioning
confidence: 99%
“…Charged particle beam-induced deposition (Matsui et al 2000, Shedd et al 1986) is widely used, for example in focused ion-beam (FIB) technology for the formation of metal layers and for the repair of semiconductor circuits. To achieve spatial resolutions better than 100 nm, electron beam-induced deposition (EBID) and etching (EBIE) have been recently explored as a technique for fabrication or repair.…”
Section: Introductionmentioning
confidence: 99%
“…2͑b͒ and 2͑c͒, the absolute deposition yield is plotted against the absolute yields of secondary electrons and sputtering, respectively. The deposition yield varies linearly with the sputtering yield having a slope of about 2.0 and an offset of about 0.09 nm 3 / ion. For constant ion energy, the deposition yield is proportional to the secondary electron yield.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, IBID is considered a very complex process with possible contributions from primary ions, sputtered atom or ions, secondary electrons ͑SEs͒ and thermal spikes. 3 Some studies relate IBID to sputtered atom impact and others to secondary electron impact. Dubner et al found that the deposition yield is proportional to the calculated stopping power and, consequently, explained IBID in terms of the energy transfer via a cascade of atom-atom collisions to adsorbed precursor molecules.…”
Section: 2mentioning
confidence: 99%
“…19 One or more types of particles can contribute to IBID. In previous work, we have observed significant deposition outside the irradiated area during IBID.…”
Section: A Effect Of Scattered Particlesmentioning
confidence: 99%